Prevalence of Hypertension, Pre-Hypertension and Associated Risk Factors in Rural Field Practice Area of a Private Medical College in South-India - Prageetha K; Koushik M; Ananthaeashwar VM; Yogesh Mohan; Timsi Jain (Medsci Publications, 2021)
Introduction: Globally hypertension is responsible for majority of mortality and morbidity among the non-communicable disease burden. A Community based cross sectional study was carried out to find the prevalence of hypertension, pre-hypertension and associated risk factors in the rural field practice area of Saveetha Medical College between January to March 2020. Methodology: The sample size calculated was 203 and equal numbers of participants between the age group of 30 to 60 years were selected from each of the 6 villages in field practice area by Stratified Random sampling method. A semi- structured pretested questionnaire was used for data collection. Results: The prevalence of hypertension and pre-hypertension was found to be 29.4% and 28.9% respectively. Major determinants of hypertension were age, marital status, diabetes mellitus, excess salt intake, sedentary lifestyle, stress, family history of hypertension and disturbed sleep pattern. Increased odds of hypertension were seen in marital status, diabetes mellitus and excess salt intake. Conclusion: Interventional measures done in the pre-hypertensive stage prevents risk of developing hypertension. Regular screening for high blood pressure, lifestyle modifications, treatment with antihypertensive medication are required to decrease the prevalence of hypertension in the community.